Serological evidence of asymptomatic infections during Escherichia coli O104:H4 outbreak in Germany in 2011. - Yanina Balabanova (Public Library of Science (PLoS), 2013)
Introduction The largest known outbreak caused by a rare hybrid strain of Shiga toxin-producing E.coli (STEC) and enteroaggregative E. coli (EAEC) (E.coli O104:H4) of serotype O104:H4 occurred in Germany in 2011. Fenugreek sprouts acted as a transmission vehicle and were widely consumed in the outbreak area at the time of the epidemic. In total 3,842 people developed a clinical illness caused by this strain; however the rates of asymptomatic infections remain unclear. We aimed to develop a serological assay for detection of E.coli O104 LPS specific antibodies and to establish the post-outbreak levels of seropositivity among people with documented exposure to contaminated sprouts. Results and discussion Developed serological assays (ELISA with 84% sensitivity, 63% specificity and Western Blot with 100% sensitivity, 82.5% specificity) identified 33% (16/49) level of asymptomatic infection. Relatively small sample size and a significant time- lapse between the onset of symptoms and serum samples collection (appr. 8 weeks) might explain the assay variability. No association was found between clinical or demographic characteristics and assay positivity. Larger studies are needed to understand the complexity of human immune response and factors influencing development of clinical symptoms. Development of intra-outbreak research plans will substantially aid the conduct of more thorough scientific investigation during an outbreak period.